Study the Effect of Filler in Flash Welding of Copper Wire on Microhardness and Microstructure (University of Thi-Qar Journal for Engineering Sciences, 2013)
The aim of this work is to recognize the bonding by flash welding of high conductor wire(2mm) which produced in UR Company of Nasseryah. The butt welding joint of this wire was completed with mixed dendritic structure including some defects (cracks and porosity). The hardness of the region is high the base structure due to existing copper oxide phase. When Filler metal alloy (silver-copper alloy) type BAg2 is used during welding the welding zone will contain three types of bonding phases, one of these phases will decrease the hardness of the structure in comparing with the base. The all structure was defect free.